1991
DOI: 10.1128/iai.59.1.295-301.1991
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin-1 and -6 in human gingival fibroblast cultures stimulated with Bacteroides lipopolysaccharides

Abstract: Normal human gingival fibroblasts stimulated in vitro by lipopolysaccharides (LPS) from oral Bacteroides species produced ceUl-free and cell-associated thymocyte-activating factors (TAF). Neutralization assays using antisera to human interleukin-la (HuIL-la), HuIL-l0, and HuIL-6 revealed that ceUl-free TAF was attributable mainly to IL-1" and that IL-6 augmented the TAF activity of IL-1" in the culture supernatant. Another factor(s), however, may also be involved in cell-free TAF. By contrast, the active entit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(93 citation statements)
references
References 36 publications
4
88
0
1
Order By: Relevance
“…This promotion seems to be caused by cytokines, such as IL-1␤, IL-6, and TNF-␣, synthesized by cells in dental tissue, such as dental mesenchymal cells and inflammatory cells. (21)(22)(23)(24)(25)(26)(27)(28) However, little is known about the integrated regulatory mechanism of the formation and function of osteoclasts in periodontitis. It has recently been suggested that OPG/OCIF, secreted locally by osteoblasts or stromal cells in bone marrow and carried from nonosseous tissue in an endocrine fashion, suppresses osteoclast maturation and activity by binding the osteoclast differentiation factor/OPG ligand (ODF/OPGL) which is a membrane-bound protein present in osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This promotion seems to be caused by cytokines, such as IL-1␤, IL-6, and TNF-␣, synthesized by cells in dental tissue, such as dental mesenchymal cells and inflammatory cells. (21)(22)(23)(24)(25)(26)(27)(28) However, little is known about the integrated regulatory mechanism of the formation and function of osteoclasts in periodontitis. It has recently been suggested that OPG/OCIF, secreted locally by osteoblasts or stromal cells in bone marrow and carried from nonosseous tissue in an endocrine fashion, suppresses osteoclast maturation and activity by binding the osteoclast differentiation factor/OPG ligand (ODF/OPGL) which is a membrane-bound protein present in osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…(2,(17)(18)(19)(20) These cytokines are produced by fibroblasts and inflammatory cells stimulated with lipopolysaccharides of bacteria infecting dental tissues and mediate tissue inflammation and bone resorption in marginal and apical periodontitis. (21)(22)(23)(24)(25)(26)(27)(28) In addition, transforming growth factor (TGF-␤) plays an important role in bone remodeling. (29,30) Previous studies have shown IL-1␤, IL-6, TNF-␣, and TGF-␤ modulate the OPG/OCIF expression in bone marrow stromal cells, osteoblastic cells, and osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] In a further study LPS derived from Bacteroides species but not E. coli was found to stimulate IL-1ß output. 45 These conflicting results suggest that factors such as the source and concentration of LPS, cell culture conditions, and the source and age of the responding fibroblast populations can all influence IL-1ß production.…”
Section: Discussionmentioning
confidence: 99%
“…LPS from Porphyromonas gingivalis, suspected to be a periodontal pathogen, induce IL-6 [9] and IL-8 [10] in human gingival ¢broblasts. The activity of the organism is believed to play an etiological role in periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharides (LPS), the major component of the outer membrane of Gramnegative bacteria, have been thought to be one of the virulent bacterial products in periodontal diseases [8]. LPS prepared from oral Gram-negative bacteria are known to induce proin£ammatory cytokines such as interleukin-1 (IL-1), IL-6 and IL-8 in human gingival ¢broblasts [9,10]. Secretion of these cytokines is an important step in in£ammatory and immune responses.…”
Section: Introductionmentioning
confidence: 99%